Ritual Dynamics and Religious Change in the Roman Empire Proceedings of the Eighth Workshop of the International Network Impact of Empire (Heidelberg, July 5-7, 2007) - Hekster, Olivier; Schmidt-Hofner, Sebastian; Witschel, Christian (Impact of Empire, 2009)
This volume presents the proceedings of the eighth workshop of the international network 'Impact of Empire', which concentrates on the history of the Roman Empire. It focuses on the impact the Roman Empire had on changes in ritual and further religious behaviour in the empire. Readership: All those interested in Roman history and history of religion, specifically the dynamics of ritual in ancient society